0781 Association Between Snoring and Anxiety in Community-dwelling School Children. (27th April 2018) - Kimura, M; Wada, H; Shirahama, R; Suzuki, Y; Suzuki, Y; Maruyama, K; Ikeda, A; Tanigawa, T
Abstract: Introduction: We previously demonstrated that sleep disordered breathing was related to behavioral problem in primary school children (Naoko S. et al. Sleep 2017; 40:1–8). However, association between snoring and anxiety among community dwelling school children in Japan remains to be elucidated. Methods: A cross sectional study on whole primary school children in a city in Japan was conducted. A questionnaire, which included questions regarding a history of snoring, anxiety and variables: such as sex, grade, height, weight, tonsil hypertrophy and asthma, was delivered to parents or guardians of all the children (26, 599) via the schools, and their responses were collected by teachers. Anxiety was evaluated with the subscale of Strengths and Difficulties Questionnaire (SDQ); the scores for emotional symptoms. Score 0 to 3 was defined as 'no anxiety', and score 4 to 10 as 'having anxiety'. Univariable and multivariable regression and logistic analyses adjusted for the variables were conducted, using SAS version 9.4 software. Results: In total, 17, 859 children were included in this analysis. The prevalence of children 'having anxiety' in 'no snoring', in 'snoring once/twice a week' and in 'snoring more than three times a week' were 6.0%(n=573), 9.7%(658) and 12.5%(176), respectively. The Odds Ratios(95% Confidence interval) for 'having anxiety' of 'snoring once/twice a week' and 'snoring more than three times a week' referenced to 'no snoring' were 1.67(1.49–1.88) and 2.19(1.82–2.63), respectively (P for trend<0.0001). Conclusion: Frequency of snoring was significantly associated with anxiety among community-dwelling school children. Support (If Any):